Penerapan Model Pembelajaran Kooperatif Tipe Teams Games Tournaments (TGT) untuk Meningkatkan Hasil Belajar Matematika Siswa Kelas V-A SDN 161 Pekanbaru - Yulsar, Winda Kamala; Witri, Gustimal; Alim, Jesi Alexander (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
AbstractThe purpose of this research is to increase the result of learning mathematics on V-A grade student of SDN 161 Pekanbaru through application cooperative learning model Teams Games Tournaments type. The main question in this research is can application of cooperative learning model Teams Games Tournaments type improve the result of studying mathematics of V-A grade SDN 161 Pekanbaru students?”. Hypothesis of this research is : if applying cooperative learning model Teams Games Tournaments type can increase learning outcome. This research consist of three cycles. Percentage of teacher’s activities in cycle I was 89,32% (very good chategory), in cycle II was 92,12% (very good chategory), in cycle III was 96,89% (very good chategory). Percentage of student’s activities in cycle I was 86,52% (very good chategory), in cycle II was 89,32% (very good chategory), in cycle III was 96,90% (very good chategory). Based on analysis data and discussion of the research the mean score of student’s learning outcome was increased. The mean of student’s outcome from 49,10 in cycle I was 63,28, in cycle II increased to 77,51, in cycle III increased to 84,44. From that data is can be coucluded that the application of cooperative learning model Teams Games Tournaments type can increase the result of studying mathematics of V-A grade students in SD Negeri 161 Pekanbaru.Keywords : Model, Cooperative Learning Teams Games Tournaments type, Mathematics achievement